Evaluation of Rheological Parameters of Slag-Based Paste Backfill with Superplasticizer. (18th January 2021) - Zhang, Zhonghui; Li, Yuanhui; Ren, Lei; Guo, Zhenbang; Jiang, Haiqiang; Liu, Na
Abstract : The use of blast furnace slag-based binders in cemented paste backfill (CPB) has become increasingly popular in China, due to its low cost and superior early-age strength. Increasing the solid content can increase the strength of CPB, but it will lead to a decrease in its fluidity. As a chemical admixture that can improve CPB slurry fluidity, superplasticizer is gaining increased interest in the field of CPB. In this study, the effects of superplasticizer types and dosages, curing time, solid content, and binder content on the rheological properties of fresh CPB made of blast furnace slag-based binder (Slag-CPB) were studied. For Slag-CPB samples, polycarboxylate (PC) has the best water-reducing effect, followed by polymelamine sulfonate (PMS) and polynaphthalene sulfonate (PNS). In the absence of a superplasticizer, the shear yield stress and plastic viscosity of Slag-CPB are lower than those of CPB made of ordinary Portland cement (OPC-CPB). The water-reducing effect of PC on OPC-CPBs samples is stronger than that of Slag-CPB samples. The degradation rate of the water-reducing effect in slag-based samples is higher than that in cement-based samples. The effect of PC is affected by solid content and binder content. These results will contribute to a better understanding of the rheological behavior of Slag-CPB with superplasticizer.